2005
DOI: 10.1254/jphs.qt-a3
|View full text |Cite
|
Sign up to set email alerts
|

QT PRODACT: In Vivo QT Assay in Anesthetized Dog for Detecting the Potential for QT Interval Prolongation by Human Pharmaceuticals

Abstract: Abstract. The purpose of this study was to assess the utility of the isoflurane-anesthetized dog model for detecting the potential for QT interval prolongation by human pharmaceuticals. The effects of 10 positive compounds with torsadogenic potential, 8 negative compounds with little torsadogenic potential, and dl-sotalol as a common positive compound were evaluated in 5 facilities in accordance with the common protocol approved by QT PRODACT. Each test compound was cumulatively infused into male beagle dogs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Although significant changes in HR including marked increases in it were occasionally observed, they were not considered to be related to the treatment since the changes were transient and no significant effect on HR was observed in anesthetized dogs (17,18). There was no significant change in QRS duration.…”
Section: Summary Of Changes In Qtcf Intervalmentioning
confidence: 99%
“…Although significant changes in HR including marked increases in it were occasionally observed, they were not considered to be related to the treatment since the changes were transient and no significant effect on HR was observed in anesthetized dogs (17,18). There was no significant change in QRS duration.…”
Section: Summary Of Changes In Qtcf Intervalmentioning
confidence: 99%
“…At such longer RR intervals, a plot of QT versus RR is almost flat, whereas the QT interval lengthened with an increase in RR interval at shorter RR intervals, suggesting that a logarithmic correction formula might be more suitable for a wide range of RR intervals. In anesthetized dogs, however, such severe bradycardia is not usually observed even when administering bradycardiac drugs (Tashibu et al, 2005). Therefore, Matsunaga's formula might show a poor fit in the present study because of the relative short range of RR intervals.…”
Section: Discussionmentioning
confidence: 67%
“…Fridericia's formula−division of the QT interval by the cube root of the RR interval-was effectively used in a large−scale QT assessment trial performed by JPMA QT PRODACT using isoflurane-anesthetized dogs (Tashibu et al, 2005). Although the group did not demonstrate the appropriateness of the formula scientifically, the study did detect the effects of clinically QT-prolonging and non-QT-prolonging drugs on QTcF interval with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this effect may be due to the presence of ketoconazole because the serum level of terfenadine increased and the concentrations of metabolite decreased, which suggested that ketoconazole inhibited terfenadine metabolism [16]. Terfenadine at 0.3 mg/kg (iv) produced no effect on the QT interval, but at 1 and 3 mg/kg, it significantly prolonged the QT interval in dogs [24]. In guinea pigs, a 10 mg/kg intravenous infusion of terfenadine also resulted in QT prolongation, and an oral dose of terfenadine (50-60 mg) in combination with ketoconazole (200 mg/kg) caused immediate prolongation [11].…”
Section: Discussionmentioning
confidence: 99%